The Effectiveness Of Atorvastatin On Kidney Function In Outpatient Diabetic Nephrophaty Patients - Hasmono, Didik; Tanasy, Marledy; Firandi, Adelia; Hartono, Ruddy; Hanum, Putri Safitri (Brawijaya University, 2023)
Introduction: Dyslipidemia can damage the kidneys through increased oxidative stress. Statins can be used as adjunctive therapy to standard treatment with ACEIs or ARBs to improve renoprotection. Objective: The study is that to analyze the effectiveness atorvastatin on changes in kidney function in patients diabetic nephropathy. Methods: It was observational study. Samples were taken prospectively from diabetic nephropathy patients receiving atorvastatin at the Interna Polyclinic of the Bhayangkara Hospital Surabaya namely November 2021 – January 2022. Patients aged 18 – 80 years received atorvastatin for ≤3 months before the study was conducted, with GFR stages 3A, 3B, and 4, with mild, moderate, and severe albuminuria degrees. Results: There are several patients which receive ARBs, namely candesartan and ketoacid which can affect the results of the analysis so that different tests are conducted in the three groups, the result shows a significant decrease in BUN values in the sample group which receives additional ketoacid therapy (p <0.05); besides, a decrease in parameters albuminuria in the group with additional 16 mg candesartan therapy which is not significant. Conclusion: The administration atorvastatin alone 20 mg or in combination with candesartan 16 mg and ketoacid on kidney function after 3 months of use can prevent the progression of diabetic nephropathy. Key words: Atorvastatin; Diabetic Nephropathy; Kidney Function